The Effect of Operational Fishing Cost Management on Fishermen's Income in Pantai Labu and Percut Sei Tuan Districts - Tiffany Tetrin Rosalin Pasaribu (Jurnal Penelitian Samudra, 2026)
Akademi Maritim Belawan tiffanybutarbutar22@gmail.com Abstract The fisheries sector plays an essential role in supporting the livelihoods of coastal communities. One of the major factors affecting fishermen's income is the effectiveness of operational fishing cost management. Poor cost management often leads to excessive operational expenditures, reducing net income despite favorable fishing yields. This study aims to examine the effect of operational fishing cost management on fishermen's income in Pantai Labu and Percut Sei Tuan Districts, Deli Serdang Regency, North Sumatra, Indonesia. This research employed a quantitative approach with an associative research design. The population consisted of 63 fishermen, while 51 respondents were selected using purposive sampling. Primary data were collected through structured questionnaires and analyzed using SPSS version 26. The analytical techniques included validity and reliability tests, classical assumption tests, simple linear regression analysis, and hypothesis testing using the t-test. The findings reveal that operational fishing cost management has a positive and statistically significant effect on fishermen's income. The regression equation obtained was Y = 3.376 + 0.729X, with a significance value of 0.000 (< 0.05). These results indicate that effective planning, recording, controlling, and evaluating operational fishing costs contribute significantly to increasing fishermen's income. Therefore, improving fishermen's financial management capabilities should become an important strategy for enhancing the economic welfare of coastal communities.